Doctors' Legal Protection of Midwives And Nurses Professionals In Medical Actions In Hospitals - Yeni Vitrianingsih; Slamet Suhartono; Yovita Arie Mangesti; Budiarsih (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
The lack of legal understanding by the parties concerned and the lack of legal protection for both patients and health workers. So the results of the nurses' hard work in providing health services if they are not successful will be faced with the law and even categorized as malpractice with criminal sanctions. Focus problems, namely: Doctors' legal protection of midwives and nurses professionals in medical actions in hospitals.The method used in this study is normative juridical research, which is a study using legislation that includes three layers of legal science consisting of the study of legal science, legal theory and legal philosophy. The results of the discussion found that the delegation of Doctor's authority to the nurse profession in medical action from a legal perspective. Nurses are someone who plays a role in caring for and helping someone by protecting them from pain, injury and the process of aging. It is not in accordance with the regulations of Law No. 38 of 2014 concerning Nursing Article 32 Paragraph (1) and Minister of Health Regulation No. 2052 of 2011 Article 23 Paragraph (1). The nature of the act of giving a medical diagnosis and the determination of medical therapy should not be delegated to nurses of Law No. 17 of 2023. The authority of nurses is as follows: Article 30 paragraph 1 and 2. The two legal umbrellas can certainly make nurses' understanding and protection in carrying out medical duties.